2020
DOI: 10.21203/rs.3.rs-108488/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Related Quality of Life of Patients with Chronic Non-Communicable Diseases During the Coronavirus Pandemic in Ethiopia: A Multi-Facility Study

Abstract: BackgroundThe Coronavirus pandemic is presenting several challenges in Ethiopia on an unprecedented scale. It is affecting the country in different ways ranging from a significant impact on the economy to a disrupted public health delivery of both curative and preventive services. The aim of this study was to assess health related quality of life of patients with chronic non-communicable diseases during the Coronavirus pandemic in Addis Ababa, Ethiopia.MethodsA multi-facility based cross sectional study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…The finding of this study is supported by other studies which report that as levels of education increase, the likelihood to have affected health-related quality is decreased [ 15 ]. The justification might be that those who, more educated might be more aware of health and practice better prevention strategies and healthy lifestyles in their lives.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The finding of this study is supported by other studies which report that as levels of education increase, the likelihood to have affected health-related quality is decreased [ 15 ]. The justification might be that those who, more educated might be more aware of health and practice better prevention strategies and healthy lifestyles in their lives.…”
Section: Discussionsupporting
confidence: 87%
“…Age, educational status, duration of treatment, presence of respiratory symptoms, and missed healthcare appointments during COVID-19 were significant variables associated with HRQOL. The finding of this study is supported by studies conducted in India, Turkey, Asia, Morocco, and Ethiopia which reported that these variables were significantly associated with health-related quality of life of patients [ 12 , 14 , 15 , 19 ]. This study identified that, the younger patients were less likely to have poor HRQOL during COVID-19 pandemic compared with elder patient, which is supported by other studies conducted in Ethiopia and Morocco [ 2 , 19 ] which were reported that younger patients were less likely had poor HRQOL compared with elder patient.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, the associations between lower HRQoL and comorbidities such as COPD, malignancy, and asthma(p<0.05), were also consistent with previous studies on Covid-19. 23 , 41 , 53 , 55 , 63 , 70 , 71 This could be due to respondents who had underlying diseases might be worried about reinfection after being discharged and avoiding both urgent or emergency and routine medical care that improves their health status. 72 This study has several strengths and added value to the current scientific research.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous studies, which found a higher burden of psychological distress and fatigue among Covid-19 survivors. 48,52,54,55 This might be due to the fact that Covid-19 survivors have anxiety/depression which is linked to worry about future careers, feelings of job insecurity, loneliness and isolation, concerns about family members, social stigma and discrimination, and workplace discrimination. [56][57][58][59] The high prevalence of anxiety/depression and fatigue among Covid-19 survivors highlighted the need for using the cost-effective psychological interventions such as cognitive behaviour therapy [CBT] that have the potential of combating anxiety/depression to improve the post-Covid-19 trauma.…”
mentioning
confidence: 99%